Jesuits and Fortifications : the Contribution of the Jesuits to Military Architecture in the Baroque Age. - De Lucca, Dennis (History of warfare, 2012)
This book sheds light on the role of Jesuit mathematicians in the widespread dissemination of ideas about military architecture in the seventeenth and eighteenth centuries, by means of teaching, writings and consultancy activities aimed at assisting Catholic leaders in their wars against protestants and infidels.